Influence of surface cooling on the deposition behavior of combusting Iron particles - Steven Floor; Jesse Hameete; XiaoCheng Mi (Applications in Energy and Combustion Science)
This work explores the impact of actively cooling the wall surface on the deposition behavior of combusting iron particles. Experiments were conducted with a Jet-in-Hot-Coflow (JHC) burner to analyze how a reduced wall temperature and wall material properties influence particle deposition behaviors. Multiple wall materials were utilized for the experiments. The deposition was quantified by measuring the deposited volume of samples using optical profilometry. The experimental results showed a clear reduction in deposition when active wall cooling was applied across all metallic wall materials under varying experiment durations. The material properties of the metal walls do impact deposition when cooling is applied, although the differences are small. Particle agglomeration is observed on cooled metal plates, suggesting a tendency for particles to adhere to other particles rather than the wall surface. Clear signs of wall melting were found on deposition plates that were not cooled. This observation suggests that cooling the wall material reduces wall melting, thereby decreasing deposition. Further testing with concrete plates uncovered that wall surface roughness can also influence deposition.